Pengaruh Pengetahuan Perpajakan, Pemahaman Pajak, Kesadaran Wajib Pajak, dan Pelayanan Fiskus Terhadap Kepatuhan Wajib Pajak UMKM (Studi Kasus Pelaku UMKM yang Terdaftar di KPP Pratama Batu) - Firda Hidayatul Fadillah; Afifudin Afifudin; Irma Hidayati (e_Jurnal Ilmiah Riset Akuntansi, 2023)
One of the tax revenues in Indonesia comes from the Micro, Small and Medium Enterprises (MSMEs) sector. But the low level of compliance of taxpayers in fulfilling their tax obligations. In this case the government gives full trust to taxpayers to calculate, pay and report their own taxes. This study aims to determine the effect of tax knowledge, tax understanding, taxpayer awareness, and tax authorities on MSME taxpayer compliance. The population of this study is MSME taxpayers who are registered at KPP Pratama Batu. This study used a purposive sampling technique for sampling. A total of 95 questionnaire data were obtained and processed with SPSS 29.0 for windows. The results of this study indicate that knowledge of taxation has a positive effect on MSME taxpayer compliance, tax understanding has a positive effect on MSME taxpayer compliance, taxpayer awareness has a positive effect on MSME taxpayer compliance and tax authorities services have no effect on MSME taxpayer compliance.Keywords: MSMEs, tax knowledge, tax understanding, taxpayer awareness, and tax authorities